Role of temperatures and solvents on hydrothermal liquefaction of Azolla filiculoides. (15th February 2021) - Biswas, Bijoy; Arun Kumar, Aishwarya; Bisht, Yashasvi; Krishna, Bhavya B.; Kumar, Jitendra; Bhaskar, Thallada
Abstract: The effects of temperatures (260–300 °C), reaction times (15–60 min), and various solvents including water (H2 O), methanol (CH3 OH), and ethanol (C2 H5 OH) were studied on hydrothermal liquefaction (HTL) of Azolla filiculoides . The products distribution in terms of bio-oil and bio-residue and its characterization were investigated. It was observed that the bio-oil yield significantly increased to 21.5–28.8 wt% under CH3 OH and C2 H5 OH solvents as compared to H2 O solvent (11–21.3 wt%). Maximum bio-oil was obtained with C2 H5 OH solvent (28.8 wt%), CH3 OH solvent (28.7 wt%) and H2 O solvent (21.5 wt%) at a temperature of 280, 260 and 280 °C for 60, 15 and 15 min reaction times, respectively. Gas Chromatography-Mass Spectrometry (GC-MS), Fourier Transform-Infrared Spectroscopy ( FT-IR) and Nuclear Magnetic Resonance ( 1 H NMR) analysis of bio-oils indicated that Azolla filiculoides was converted to various valuable compounds including aromatics, nitrogenated and oxygenated compounds. Total organic carbon (TOC) of aqueous phase was observed to be highest at 31, 000 mg/L liquefaction with water solvent, but when alcoholic solvent was used it decreased to 23, 000–21, 000 mg/L. However, opposite trend was observed in the case of total nitrogen (TN) concentration. The bio-residues characterization showed that the different solvents had different effects on biomass macromolecule decomposition into products. Highlights: Different solvents were screened in HTL of Azolla filiculoides. Maximum bio-oil of 28.8 wt% was obtained with ethanol as a solvent. Ethanol and methanol were significantly enhanced the decomposition of Azolla. Long chain ester compound was obtained in alcoholic solvents liquefaction bio-oil.